New distribution data, new species and two new genera of Aleocharinae from Tropical Africa (Coleoptera, Staphylinidae). - Pace, Roberto (Contributions to Entomology = Beiträge zur Entomologie, 2013)
Nine tribes (Pronomaeini, Pygostenini, Gyrophaenini, Diestotini, Falagriini, Athetini, Lomechusini, Thamiaraeini, Aleocharini), 15 genera (Nopromaea, Typhloponemys, Brachida, Diestota, Falagria, Ischnopoda, Atheta, Brachycraspedusa, Catarractodes, Brachysipalia, Diplopleurus, Zyras, Paramyrmoecia, Spaniodmoinusa, Aleochara) and 26 species are recognized in the material studied. Nineteen species, two genera, Brachycraspedusa n. gen. of the tribe Athetini and Spaniodmoinusa n. gen. of the tribe Thamiaraeini, are described as new to science: Nopromaea nakuruensis n. sp., Nopromaea cornelli n. sp., Brachida burkinensis n. sp., Diestota doulaensis n. sp., Falagria bartolozzii n. sp., Ischnopoda riftensis n. sp., Atheta senecicola n. sp., Atheta willersi n. sp., Brachycraspedusa naivashaensis n. sp., Catarractodes cristatus n. sp., Brachysipalia melanica n. sp., Diplopleurus maculipennis n. sp., Diplopleurus intermedius n. sp., Zyras paraopticus n. sp., Zyras taitaorum n. sp., Zyras trinus n. sp., Zyras digorum n. sp., Zyras triumbonatus n. sp., and Spaniodmoinusa cornelli n. sp. All new species and the new genera are illustrated and compared with similar described species or genera.KeywordsInsecta, Coleoptera, Staphylinidae, Aleocharinae, taxonomy, new genera, new species, Kenya, Burkina Faso, Cameroon, Zambia.Nomenclatural ActsBrachycraspedusa Pace, 2013 (Aleocharinae), gen. nov.Spaniodmoinusa Pace, 2013 (Aleocharinae), gen. nov.senecicola Pace, 2013 (Atheta (Oxypodera)), spec. nov.willersi Pace, 2013 (Atheta (Oxypodera)), spec. nov.burkinensis Pace, 2013 (Brachida), spec. nov.naivashaensis Pace, 2013 (Brachycraspedusa), spec. nov.melanica Pace, 2013 (Brachysipalia), spec. nov.cristatus Pace, 2013 (Catarractodes), spec. nov.doualensis Pace, 2013 (Diestota), spec. nov.intermedius Pace, 2013 (Diplopleurus), spec. nov.maculipennis Pace, 2013 (Diplopleurus), spec. nov.bartolozzi Pace, 2013 (Falagria (Leptagria)), spec. nov.riftensis Pace, 2013 (Ischnopoda), spec. nov.cornelli Pace, 2013 (Nopromaea), spec. nov.nakuruensis Pace, 2013 (Nopromaea), spec. nov.cornelli Pace, 2013 (Spaniodmoinusa), spec. nov.triumbunatus Pace, 2013 (Zyras (Androdonia)), spec. nov.digorum Pace, 2013 (Zyras (Camonia)), spec. nov.paraopticus Pace, 2013 (Zyras (Camonia)), spec. nov.taitaorum Pace, 2013 (Zyras (Camonia)), spec. nov.trinus Pace, 2013 (Zyras (Camonia)), spec. nov.